Strategi Meningkatkan Motivasi Belajar Peserta Didik - Irma Julita; Neviyarni Neviyarni; Herman Nirwana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Learning motivation plays a crucial role in determining students' success in the educational process. This article aims to systematically examine various effective strategies for enhancing students' learning motivation through a literature review approach. The study employs a qualitative method based on library research by analyzing relevant scholarly sources, including journals, books, and previous research findings. The results indicate that learning motivation is influenced by both internal and external factors and can be improved through several strategies, such as the implementation of active learning methods, the use of educational technology, social and environmental support, personalized learning approaches, and the application of reinforcement and appreciation. The study concludes that collaboration between teachers, students, parents, and schools is essential to creating a supportive environment that fosters intrinsic learning motivation. This article is expected to provide practical insights for the development of more adaptive and relevant teaching methods tailored to students' needs.